Pemanfaataan Instagram Di Star Radio Tangerang - Suharti Suharti; Makroen Sanjaya (Universitas Katolik Widya Karya Malang, 2023)
Social media is currently in demand by many people. Star Radio Tangerang utilizes Instagram social media to promote its broadcast programs so that listeners do not find it difficult to continue listening to their broadcasts. The purpose of this research is to find out the utilization of Instagram social media at Star Radio Tangerang in promoting broadcast programs for its listeners and to find out how the feedback obtained after utilizing Instagram social media. This research uses Social Media theory, using a qualitative approach, and descriptive method. Data collection techniques were carried out through documentation, observation, literature study, and in-depth interviews. The results of this study show social media as a medium for socialization between broadcasters and listeners, making it easier for them to access and listen to broadcasts. Social media is proven to be the latest development of new internet-based web development technology, which makes it easier for everyone to communicate, participate, share and form a network online.